How rotation affects matter dynamics around black holes. (Research'eu results magazine)
The REGMAT project has explored the interplay between matter and the rotation of spacetime thanks to novel methods. Project results not only further our understanding of black holes, but also have implications for research on thermalisation in strongly coupled quantum theories.